Catch ancient maps exhibit mapping the Philippine seas - Yamsuan, Cathy Canares
More than geography and political territories, ancient maps tell stories about history, conflict, culture, trade and even myths. Juan Layas exhibit at the Metropolitan Museum showcases rare historical maps and charts of the archipelago drawn from the early 16th century to the end of the 19th century.
Keywords: Maps -- Philippines